2020
DOI: 10.21307/acee-2020-011
|View full text |Cite
|
Sign up to set email alerts
|

Application of Potassium Ferrate(VI) in the Treatment of Selected Water and Wastewater Pollutants – Short Review

Abstract: The paper presents the application of potassium ferrate(VI) (K2FeO4 ) for the removal of selected pollutants from water and wastewater. The research results on the degradation of endocrine disrupting compounds (EDCs), decomposition of surfactants (SPCs), personal care products (PCPs), pharmaceuticals and their metabolites have been reviewed. Due to K2FeO4 strong oxidizing and coagulating properties, high stability, non–toxic by–products and non–selectivity it is sometimes called “environmentally friendly oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The generated test results correspond to the literature data, which indicate that the value of the redox potential for the FeO 4 2− ion is greater in an acidic environment than in a neutral environment (E • = +2.20 V in acidic and E • = +0.72 V in neutral media). Generally, greater efficiency of the oxidation of organic compounds can be observed, while conducting the oxidation process in an acidic environment, rather than in a neutral one [43,44]. Another study indicated that use of K 2 FeO 4 for the purification of highly polluted tannery wastewater from leather dyeing processes resulted in the discoloration (98.4% removal), chemical oxygen demand (77.2% removal), total organic carbon (75.7% removal), and suspended solids (96.9% removal); the reported values were the smallest when 1.200 g/L K 2 FeO 4 at pH 3 within 9 min was used [59].…”
Section: Ccd/rsm Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generated test results correspond to the literature data, which indicate that the value of the redox potential for the FeO 4 2− ion is greater in an acidic environment than in a neutral environment (E • = +2.20 V in acidic and E • = +0.72 V in neutral media). Generally, greater efficiency of the oxidation of organic compounds can be observed, while conducting the oxidation process in an acidic environment, rather than in a neutral one [43,44]. Another study indicated that use of K 2 FeO 4 for the purification of highly polluted tannery wastewater from leather dyeing processes resulted in the discoloration (98.4% removal), chemical oxygen demand (77.2% removal), total organic carbon (75.7% removal), and suspended solids (96.9% removal); the reported values were the smallest when 1.200 g/L K 2 FeO 4 at pH 3 within 9 min was used [59].…”
Section: Ccd/rsm Findingsmentioning
confidence: 99%
“…Due to the fact that the decomposition products of K 2 FeO 4 are iron oxides and oxygen, it is defined as a green oxidant and can be a promising alternative to the conventional coagulants [42]. Among others, potassium ferrate (VI) has been engaged for degradation of endocrine-disrupting compounds (EDCs), decomposition of surfactants (SPCs), personal care products (PCPs), pharmaceuticals [43], and also for oxidation of cyanides (CN − ) originating from the mining and processing of gold ore, degradation of natural organic matter (NOM), oxidation of N,N-diethyl-3-toluamide (DEET), many dyes (Methylene Blue, Orange II, Brilliant Red X-3B, Acid Green 16), removal of algae [44] and for wastewater treatment [45].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that for carwash wastewater the temperature is in the range of 28 to 30°C, pH of 5.9 to 8.8, total suspended solids (TSS) from 265 to 794 mg/L, chemical oxygen demand (COD) from 320 to 1019 mg O2/L, oil and grease from 180 to 200 mg/L, turbidity from 118 to 380 NTU, and electrical con-ductivity from 84 to 100 μS/cm [3]. Recently, K2FeO4, a green chemical, is frequently proposed for the treatment of various types of wastewater and waste [4][5][6]. Because of thet, the aim of this paper is to examine the suitability of K2FeO4 as a green alternative, in the treatment of carwash wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Iron (VI) compounds may be utilized as inhibitory additives since the degree of corrosion prevention reached 60% [18]. It can be used as a multifunctional chemical for the treatment of water and wastewater and is a substantial substitute for advanced oxidation techniques (AOP) [19].…”
Section: Introductionmentioning
confidence: 99%